DESIGN AND DEVELOPMENT OF VIDEO TESTIMONY COVID-19 SURVIVOR WITH EDITING CONTINUITY CUTTING TECHNIQUES - Deli Deli; Donny Zhang (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Over time, on December 30, 2019, a group of patients with an unknown pneumonia disease were observed in Wuhan, China, and reported to the China bureau of the World Health Organization (WHO) in Beijing. Patients with COVID-19 infection were shown to have a reaction to the average age of 55 years and a rare reaction to the age of children. The reactions of COVID-19 sufferers will occur such as fever, dry cough, shortness of breath, and the most severe case is suffering from pneumonia. Documentary is a story that uses a model as a representation of factual events. Documentary videos have the potential to convey complex information effectively, especially when used in innovative ways by taking into account their needs, to find out a story from another person who is a survivor of COVID-19, and to convey that story to the public as knowledge and awareness raising against COVID -19, which is supported by a documentary as a representation of factual events, using Adobe Premiere Pro CC 2017 with the Editing Continuity Cutting technique, which is posted to youtube.